Molecular Cloning and Functional Characterization of a β-Glucosidase Gene to Produce Platycodin D in Platycodon grandiflorus - Su, Xinglong; Meng, Fei; Liu, Yingying; Jiang, Weimin; Wang, Zhaojian; Wu, Liping; Guo, Xiaohu; Yao, Xiaoyan; Wu, Jing; Sun, Zongping; Zha, Liangping; Gui, Shuangying; et al. (Frontiers in Plant Science, 2022)
Platycodin D (PD) is a deglycosylated triterpene saponin with much higher pharmacological activity than glycosylated platycoside E (PE). Extensive studies in vitro showed that the transformation of platycoside E to platycodin D can be achieved using β-glucosidase extracted from several bacteria. However, whether similar enzymes in Platycodon grandiflorus could convert platycoside E to platycodin D, as well as the molecular mechanism underlying the deglycosylation process of platycodon E, remain unclear. Here, we identified a β-glucosidase in P. grandiflorus from our previous RNA-seq analysis, with a full-length cDNA of 1488 bp encoding 495 amino acids. Bioinformatics and phylogenetic analyses showed that β-glucosidases in P. grandiflorus have high homology with other plant β-glucosidases. Subcellular localization showed that there’s no subcellular preference for its encoding gene. β-Glucosidase was successfully expressed as 6 × His-tagged fusion protein in E. coli BL21 (DE3). Western blot analysis yielded a recombinant protein of approximately 68 kDa. In vitro enzymatic reactions determined that β-glucosidase was functional and could convert PE to PD. RT-qPCR analysis showed that the expression level of β-glucosidase was higher at night than during the day, with the highest expression level between 9:00 and 12:00 at night. Analysis of the promoter sequence showed many light-responsive cis-acting elements, suggesting that the light might regulate the gene. The results will contribute to the further study of the biosynthesis and metabolism regulation of triterpenoid saponins in P. grandiflorus.